If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = 4w * 3 Reorder the terms for easier multiplication: 24 = 4 * 3w Multiply 4 * 3 24 = 12w Solving 24 = 12w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-12w' to each side of the equation. 24 + -12w = 12w + -12w Combine like terms: 12w + -12w = 0 24 + -12w = 0 Add '-24' to each side of the equation. 24 + -24 + -12w = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -12w = 0 + -24 -12w = 0 + -24 Combine like terms: 0 + -24 = -24 -12w = -24 Divide each side by '-12'. w = 2 Simplifying w = 2
| -2=6a-4 | | 12x-7=24x+2 | | 2*56=-4 | | 2/5(25)-8=1/5(25)+7 | | 120w-23w=691 | | 1.25-0.3k+.5=1.3+0.5k | | 12x=11x-23 | | P-4+6+7p=74 | | 120w+23w=691 | | (-4-7)+1= | | b/13-3b/13=8/3 | | -16+18=-2(x+6) | | -4=-1-3 | | .5(4x+14)=2(2x-7) | | 125c^2-180= | | .4y+6=31 | | 0.5x-0.75y=-2 | | 9=6(x+6)-7x | | h=160t-16t^2 | | -22-7x=48 | | 4(x-1)-4=2x+2(-3+x) | | u/4=-8 | | 9-0.7k=9 | | 2.37=.87h-.25 | | -5(6+5p)=136 | | -9x-36=90 | | 1+x+7-9x=-24 | | 16x-2=40x+16 | | 22=13+x | | 8a+3(-7)=3 | | -2b/13=8/3 | | a^12=5 |